Exponential stability of a class of nonlinear systems via fixed point theory. (July 2020) - Chen, Lili; Liu, Xin; Zhao, Yanfeng
Abstract: In this paper, the problem of globally stochastically exponential stability in the p th moment for a class of T–S fuzzy stochastic impulsive genetic regulatory networks with random discrete delays, distributed delays and parameter uncertainties is discussed. By utilizing the theory of stochastic analysis, semigroup theory and fixed point theory, a novel sufficient condition to guarantee the globally stochastically exponential stability in the p th moment of the considered genetic regulatory networks is derived. Eventually, an example is given to demonstrate that the obtained result is effective.